Study of the Concept of Curriculum Relationship with Learning - Sabriadi HR; Nurul Wakia (Institusi Agama Islam Negeri (IAIN) Bone, 2026)
This research aims to explore the relationship between curriculum and learning in the context of education that continues to evolve. Education that is adaptive and relevant to the demands of the times is the key in preparing future generations to face increasingly complex challenges. Therefore, a well-designed curriculum has an important role in increasing learning effectiveness and achieving student learning outcomes. This study adopts a qualitative approach with an exploratory study design to understand more deeply about the relationship between curriculum and learning. This study uses literature as the primary source of data, which is obtained through various sources such as e-books, articles, and textbooks. Triangulation techniques are used in data collection and analysis to ensure the validity and validity of the data obtained. The results of the study show that curriculum and learning are closely related, where the curriculum functions as a guideline in designing effective learning strategies. The integration of innovative teaching methods and continuous assessment is an important factor in improving a relevant and effective learning experience. This research also suggests that the curriculum be developed in a responsive manner to meet the social demands and needs of students in facing the world of work. Thus, this study provides insight into how curriculum design can affect the learning process and student learning outcomes, as well as providing recommendations for better and more relevant curriculum development